2021
DOI: 10.21037/atm-21-1303
|View full text |Cite
|
Sign up to set email alerts
|

Wuzhi capsule increased systemic exposure to methotrexate by inhibiting the expression of OAT1/3 and P-gp

Abstract: Background: Methotrexate (MTX) is an important anticancer agent and immunosuppressant with a narrow therapeutic window. Wuzhi capsule (WZC) is an extract of Schisandra which is widely used to treat liver diseases. Co-administration of MTX and WZC is common in the clinical setting, but research on the interaction between WZC and MTX is limited. This study aimed to investigate the effects of WZC on the pharmacokinetics of MTX in rats and to explore the role of membrane transport proteins OAT1/3 and P-gp in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It was found that when both substances were administered simultaneously, Wuzhi capsule decreased CLz/F and Vz/F of methotrexate and increased Cmax. In addition, the administration of S. sphenanthera extract inhibited the expression of OAT1/3 proteins in the kidneys and P-gp in the small intestine, which may suggest the future use of this combination to reduce inflammation when administering immunosuppressive drugs [ 152 ]. The latest research shows that in the future, the combination of the Wuzhi capsule with anti-cancer drugs will be widely available and recommended.…”
Section: Dbcls As Potential Chemotherapeutic Adjuvantsmentioning
confidence: 99%
“…It was found that when both substances were administered simultaneously, Wuzhi capsule decreased CLz/F and Vz/F of methotrexate and increased Cmax. In addition, the administration of S. sphenanthera extract inhibited the expression of OAT1/3 proteins in the kidneys and P-gp in the small intestine, which may suggest the future use of this combination to reduce inflammation when administering immunosuppressive drugs [ 152 ]. The latest research shows that in the future, the combination of the Wuzhi capsule with anti-cancer drugs will be widely available and recommended.…”
Section: Dbcls As Potential Chemotherapeutic Adjuvantsmentioning
confidence: 99%
“…Organic anion transporter 3 (OAT3) is an important transporter that located in the basolateral membrane of proximal renal tubules. OAT3 plays vital parts in removing a variety of drugs from the kidney, so as to avoid their possibly toxic side effects in the body (Fu et al, 2021). Activated OAT3 attenuates renal lipid accumulation and alleviates renal injury associated with renal inflammation and fibrosis in high-fat diet-induced obese rats (Pengrattanachot et al, 2020).…”
Section: Oat3-mediated Transfer Channelsmentioning
confidence: 99%